Effects of sustained isometric handgrip on praecordial accelerocardiogram in normal subjects and in patients with heart disease. Issue 8 (August 1975) - Hume, L; Irving, J B; Kitchin, A H; Reuben, S R
Abstract : The effects of isometric exercise on the maximum amplitude of the praecordial accelerocardiogram (as represented by the DE deflection) have been compared in 6 normal subjects (group 1), 12 patients with aortic stenosis (group 2), and 16 patients with myocardial disease (group 3). Whereas the tachycardia and pressor effects of isometric exercise were identical in all three groups, the normal subjects showed a significant decrease in DE during handgrip of 10 +/- 4 per cent (P less than 0.05) as compared with the insignificant increases of 8.5 +/- 6 per cent (P greater than 0.5), and 4 +/- 3.5 per cent (P greater 0.3) observed in the patients in groups 2 and 3. This response in the normal subjects differed significantly from the responses observed in the patients in groups 2 (P less than 0.02) and 3 (P less than 0.01). Of the patients in each of groups 2 and 3, 50 per cent responded abnormally to handgrip in that they showed a significant increase in DE. In the patients with aortic stenosis this subgroup of patients differed from the remainder in that they had a higher resting cardiac index (P less than 0.05). In the patients with myocardial disease this subgroup was characterized by a significantly lower resting left ventricular end-diastolic pressure (P less than 0.02). It seems, therefore, that those patients who increase DE in response to handgrip tend to have better left ventricular function at rest than those who do not. We suggest that this may be because of increased beta adrenergic activity at rest and during isometric exercise in the subgroup who respond to handgrip with an increase in DE.